Child welfare services for minority ethnic families : the research reviewed - Thoburn, June (Jessica Kingsley Publishers, 2005)
Based on extensive studies into child welfare services, this important book brings together research into what works in service provision for minority ethnic families. Reviewing studies of the nature and adequacy of the services provided, and the outcomes for the children and their families, this book provides much-needed guidance for policy and practice around issues of cultural and ethnic background and identity, and puts forward suggestions for future research. The authors consider in particular: the complex needs and identities of minority ethnic families who might use child welfare servic.